Clinical outcomes of children with rheumatic heart disease. Issue 8 (2nd February 2022) - Zimmerman, Meghan; Kitooleko, Samalie; Okello, Emmy; Ollberding, Nicholas; Sinha, Pranava; Mwambu, Tom; Sable, Craig; Beaton, Andrea; Longenecker, Chris; Lwabi, Peter
Abstract : Objective: To evaluate the long-term clinical outcomes of children with rheumatic heart disease (RHD) in Uganda, and determine characteristics that predict adverse outcomes. Methods: This retrospective cohort study evaluated the risk of death in Ugandan children with clinical RHD from 2010 to 2018; enrolling children aged 5–18 years old from an existing registry. Demographic data and clinical data (baseline complications, RHD severity, cardiac interventions) were collected. The primary outcome was survival. Univariable and multivariable hazard ratios (HR) were obtained from Cox proportional hazards regression. Survival probabilities were developed using Kaplan-Meier curves; log-rank tests compared survival based on cardiac interventions, disease severity and time of enrolment. Results: 612 cases met inclusion criteria; median age 12.8 years (IQR 5.3), 37% were male. Thirty-one per cent (187 of 612) died during the study period; median time to death 7.8 months (IQR 18.3). In univariable analysis, older age (HR 1.26, 95% CI=1.0 to 1.58), presence of baseline complications (HR 2.06, 95% CI=1.53 to 2.78) and severe RHD (HR 5.21, 95% CI=2.15 to 12.65) were associated with mortality. Cardiac intervention was associated with a lower risk of mortality (HR 0.06, 95% CI=0.02 to 0.24). In multivariable models, baseline complications (HR 1.78, 95% CI=1.31 to 2.41), severe RHD (HR 4.58, 95% CI=1.87 to 11.23) and having an intervention (HR 0.05, 95% CI=0.01 to 0.21) remained statistically significant. Kaplan-Meier survival curves demonstrated >25% mortality in the first 30 months, with significant differences in mortality based on intervention status and severity of disease. Conclusions: The mortality rate of children with clinical RHD in Uganda exceeds 30%, over an 8-year time frame, despite in-country access to cardiac interventions. Children at highest risk were those with cardiac complications at baseline and severe RHD.